Fodder biomass, nutritive value, and grain yield of dual‐purpose improved cereal crops in Burkina Faso. (2nd November 2021) - Zampaligré, Nouhoun; Yoda, Gildas; Delma, Jethro; Sanfo, Abroulaye; Balehegn, Mulubrhan; Rios, Esteban; Dubeux, José C.; Boote, Ken; Adesogan, Adegbola T.
Abstract: In Burkina Faso, availability of quality feed is the major constraint on livestock productivity. Adoption of improved cereal cultivars among farmers could enhance fodder supply. This study assessed the potential for improved cereal cultivars to provide food and feed. The study sites were located in the Köppen climate Zone B (Katchari and Saria) and Köppen climate Zone A (Farakoba) in Burkina Faso (Beck et al., 2018). Five cultivars of pearl millet [ Pennisetum glaucum (L.) R. Br.], nine cultivars of sorghum [ Sorghum bicolor (L.) Moench], and four cultivars of maize ( Zea mays L.) were grown during two rainy seasons. Grain yield and forage biomass were assessed, and samples analyzed for nutritive value using near infrared spectrometry (NIRS). For pearl millet, MISARI‐1 produced greatest grain yield (1.7, 2.2, and 2.6 Mg DM ha –1, for Katchari (Zone B), Saria (Zone B), and Farakoba (Zone A), respectively) and its fodder biomass averaged 4.0 Mg DM ha –1 across sites. For sorghum, Sariasso‐14, Sariasso‐16, and ICSV1049, produced the greatest grain yield in Saria (Zone B) (1.2–1.6 Mg DM ha –1 ) and Farakoba (Zone A) (1.1–1.9 Mg DM ha –1 ). Sorghum cultivars SF15, M67‐M2, and Ponta negra produced more than 5.0 Mg DM ha –1 of fodder across locations. Maize cultivars only differed in fodder biomass, with cultivar Wari producing 4.3 Mg DM ha –1 in Farakoba. The stover of the three species had high fiber, low digestibility, and crude protein concentration ranged from 40 to 94 g kg –1 . Fodders from dual‐purpose cereals are valuable feed resources for crop–livestock systems in the Sahel region. Adoption of improved food–feed cultivars has potential to increase fodder productivity and feed quality for livestock, enhancing livelihood of small‐holder farmers in Burkina Faso. Core Ideas: Improved dual‐purpose cultivars for grain and fodder can boost livestock productivity in Burkina Faso. Cultivar recommendations are location‐specific due to genotype × environment interactions. Misari‐1 and ICMV16701 millet cultivars had the highest grain yield, while Misari‐1 produced the highest fodder mass. Forage‐type sorghum cultivars produced high fodder biomass, but limited grain, which might reduce adoption. Maize cultivars did not differ in grain yield, but Wari had greatest fodder mass.